Modeling of weather data for the east Anatolia region of Turkey - Akpinar, S.; Akpinar, Ebru K. (Universidade Federal da Paraiba, 2010)
Monthly average daily data of climatic conditions over the period 1994-2003 of cities in the east Anatolia region of Turkey is presented. Regression methods are used to fit polynomial and trigonometric functions to the monthly averages for nine parameters. The parameters namely temperature, maximum-minimum temperature, relative humidity, pressure, wind speed, rainfall, solar radiation and sunshine duration are useful for renewable energy applications. The functions presented for the parameters should enable determination of specific parameter values and prediction of missing values. They also provide some insight into the variation of these parameters. The models developed can be used in any study related to climatic and its effect on the environment and energy. © 2010 Journal of Urban and Environmental Engineering (JUEE). All rights reserved.
Keywords: Energy; Environment; Maximum-minimum temperature; Pressure; Rainfall; Relative humidity; Solar radiation; Sunshine duration; Temperature; Weather parameters; Wind speed